A Tentative Design Guideline for a New Steel Beam Connection Detail to Composite Tube Columns - Azizinamini, Atorod; Prakash, Bangalore (Engineering Journal, 1993)
Steel tubes of relatively thin wall thickness filled with high strength concrete have been used in building construction in the U.S. and Far East Asian countries. This structural system allows the designer to maintain manageable column sizes while obtaining increased stiffness and ductility for wind and seismic loads. Column shapes can take the form of tubes or pipes as required by architectural restrictions. Additionally, shop fabrication of steel shapes helps insure quality control. In this type of construction, in general, at each floor level heavy steel beam is framed to these composite columns. Often, these connections are required to develop shear yield and plastic moment capacity of the beam simultaneously. This paper summarizes results and recommendations from a pilot study conducted to develop a moment-resisting steel connection detail for connecting steel beams to composite columns of the type described above. The focus of this pilot study was on composite columns having a square or rectangular cross section.